2020
DOI: 10.3390/ijerph17218088
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Knowledge, Attitudes, and Practices Related to Oral Care Among the Elderly in Hong Kong Community

Abstract: Background: The oral health of elderly populations is a significant concern, as it is closely linked to general health and health-related quality of life. Poor oral health exacerbates oral diseases, leading to an increased risk of non-communicable diseases and self-care dependence, particularly in the elderly, worldwide. Knowledge, attitudes, and practices (KAP) play influential roles in individual oral care. However, the evidence of KAP related to oral care among the elderly is still inadequate. Objective: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
4
19
1
2
Order By: Relevance
“…The data obtained based on the results of research on 35 elderly people at the Hargo Dedali Nursing Home in Surabaya showed the average value of dental and oral health knowledge was 48.1 from the maximum value, which was 100. This study is in line with research by Wong [20],…”
Section: Discussionsupporting
confidence: 93%
“…The data obtained based on the results of research on 35 elderly people at the Hargo Dedali Nursing Home in Surabaya showed the average value of dental and oral health knowledge was 48.1 from the maximum value, which was 100. This study is in line with research by Wong [20],…”
Section: Discussionsupporting
confidence: 93%
“…Notably, we found that the levels of oral health knowledge and attitudes were not coordinated. Oral health knowledge was also shown to be poor compared to oral health attitudes and practices in the study by Wong et al (2020) [ 30 ]. This may be attributed to the fact that people are increasingly concerned about their physical health as well as their quality of life, and participants had positive attitudes towards oral health, but their knowledge of oral health was limited due to their education level [ 31 ], monthly household income [ 32 ] and permanent home address [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that oral health is subjected to individual knowledge, attitudes, and practices related to oral health care. 19 Thus, understanding this population's KAP is required to develop tailored oral health educational interventions to improve their children's oral health.…”
Section: Palabras Clavementioning
confidence: 99%